Optimization of the Enzymatic Saccharification Process of Empty Fruit Bunch Pretreated with Laccase Enzyme - Rashid, Shah Samiur; Ishmael, Ukaegbu Chinonso; Jaya Vejayan, Palliah; Mohammed Fazli, Farida Asras; Sharifah Suhaiza, Nik Wan Ahmad (North Carolina State University, 2016)
The saccharification of laccase-pretreated empty fruit bunch (EFB) was optimized in a lab-scale experiment using one-factor-at-a-time (OFAT) and response surface methodology (RSM). After pretreatment, the degree of delignification was checked by noting the weight loss (%) after pretreatment, and also by the quantity of total sugar produced after saccharification with cellulase enzyme. OFAT studies of saccharification of the pretreated EFB showed that the biomass was best saccharified using cellulase enzyme at the following conditions: enzyme concentration of 30 IU/g of EFB, substrate concentration of 5.0% w/v, 50 °C, saccharification time of 24 h, and pH 5. This combination exhibited the highest yield of total sugar (28% w/w). Although 29% w/w yield was achieved with an enzyme concentration of 40 IU/g of EFB, this increase in yield was not proportional to the increased enzyme concentration and, therefore, was considered insignificant. Statistical analysis of the combined effects of pH and temperature showed that pH had a more significant effect than the temperature on the saccharification process, based on a P < 0.05 significance level. The effect of pH on total sugar production was more significant than the temperature in both linear and quadratic functions. In sum, the saccharification of laccase-pretreated EFB should follow the optimized process conditions achieved in the current study.